The Consequences of Tongue Piercing on Oral and Periodontal Tissues. (29th January 2014) - Plastargias, Ioannis; Sakellari, Dimitra
Abstract : This paper is discussing the potential consequences that may arise by the implementation of piercing in the oral cavity and is also categorizing the consequences according to their extent and severity. Furthermore, this paper is reviewing some possible oral hygiene methods that can prove to be auxiliary in decreasing the potential complications arising from oral piercing. This literature review is based on articles published from 1985 to 2012.